Identifying the Strata of Sago Stands Using Unmanned Aerial Vehicle Data (Case Study: Ambon Island, Maluku, Indonesia) - Hatulesila, Jan; Gun, Mardiatmoko; Wody, Timisela (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Manual measurements to estimate the height and diameter of sago stems can be performed directly. However, estimates of height and diameter from land cover using remote sensing or aerial photographic coverage have not been widely featured in articles at home or abroad. To determine the potential and distribution of sago plant species that can be produced per area in the sago forest area, we mapped the sago land area using drone aircraft to cover the sago land area. We determined the diameter and height classes of sago plants using a Digital Surface Model (DSM) data application method. The results of the analysis showed that there was a distribution of diameter and height of sago plants varying according to height, namely for strata-level seedlings (0 to 6 m) as much as 100, saplings (6 to 12 m) as much as 818, poles (12 to 18 m) as much as 3,332, and trees (> 18 m) as much as 3.79. for the area of sago land mapped, and can be processed into an orthomosaic covering an area of 126,883 ha.